Effects of fermented feeds and ginseng polysaccharides on the intestinal morphology and microbiota composition of Xuefeng black-bone chicken. - Yueqin Xie; Jie Liu; Huan Wang; Junyi Luo; Ting Chen; Qianyun Xi; Yongliang Zhang; Jiajie Sun (PLoS ONE, 2020)
Fermented feeds contain abundant organic acids, amino acids, and small peptides, which improve the nutritional status as well as the morphology and microbiota composition of the intestine. Ginseng polysaccharides exhibit several biological activities and contribute to improving intestinal development. Here, Xuefeng black-bone chickens were fed a basal diet fermented by Bacillus subtilis, Saccharomyces cerevisiae, Lactobacillus plantarum, and Enterococcus faecium, with or without ginseng polysaccharides. The 100% microbially fermented feed (Fe) and 100% microbially fermented feed and ginseng polysaccharide (FP) groups showed significantly increased villus height and villus height to crypt depth ratio, and decreased crypt depth in the jejunum. In the 100% complete feed and ginseng polysaccharide (Po) group, the villus height to crypt depth ratio was significantly increased, crypt depth was reduced, and villus height remained unaffected. Next, we studied the intestinal microbial composition of 32 Xuefeng black-bone chickens. A total of 10 phyla and 442 genera were identified, among which Firmicutes, Proteobacteria, and Bacteroidetes were the most dominant phyla. At the genus level, Sutterella and Asteroleplasma abundance increased and decreased, respectively, in the FP and Po groups. Sutterella abundance was positively correlated to villus height and villus height to crypt depth ratio, and negatively correlated to crypt depth, and Asteroleplasma abundance was positively correlated to crypt depth and negatively correlated to villus height to crypt depth ratio. At the species level, the FP group showed significantly increased Bacteroides_vulgatus and Eubacterium_tortuosum and decreased Mycoplasma_gallinarum and Asteroleplasma_anaerobium abundance, and the Po group showed significantly increased Mycoplasma_gallinarum and Asteroleplasma_anaerobium abundance. Moreover, bacterial abundance was closely related to the jejunum histomorphology. Asteroleplasma_anaerobium abundance was positively correlated with crypt depth and negatively correlated with villus height to crypt depth ratio. Mycoplasma_gallinarum abundance was positively correlated to villus height, and Bacteroides_vulgatus and Eubacterium_tortuosum abundance was positively correlated with villus height to crypt depth ratio and negatively correlated with crypt depth. Therefore, fermented feeds with ginseng polysaccharides may be used as effective alternatives to antibiotics for improving intestinal morphology and microbial composition.